Negotiating English Teaching Internships in a Resource-limited Islamic School: Challenges, Strategies, and Transformative Learning of Pre-Service EFL Teachers - Jinan, Khoirunnisa Aliya; Lestari, Ika Wahyuni (UIN Salatiga, 2026)
Teaching internships play a crucial role in preparing student teachers for the transition from theoretical learning to practical teaching in real classrooms. For many English as a foreign language (EFL) student teachers placed in Islamic high schools with limited resources, internships can become complex learning environments influenced by structural constraints, inadequate mentor support, and insufficient institutional support. Understanding how student teachers navigate these conditions is essential for strengthening teacher education programs in Indonesia. This study examines the challenges faced by EFL student teachers during teaching internships in a resource-limited Islamic high school, the strategies they use to overcome these challenges, and how these experiences facilitate transformative learning. Using a qualitative case study design, five third-year student teachers from the Department of English Education participated in this study. Data were collected through semi-structured interviews and reflective internship documents. The findings reveal three main challenges: inadequate school facilities, difficulties in classroom management, and limited mentoring support. In response, student teachers implemented various adaptive strategies, including student-centered teaching, engaging and joyful learning activities, collaborative group work, and contextual teaching practices suitable for the Islamic school setting. Beyond overcoming classroom difficulties, these strategies serve as reflective tools that enable student teachers to critically evaluate their assumptions about teaching and learning. Through continuous reflection, experimentation, and adaptation, participants experience a perspective shift in characteristic of transformative learning, which contributes to the reconstruction of their professional identities as EFL teachers. This study extends the application of transformative learning theory to a resource-limited Islamic high school setting and emphasizes the importance of institutional support, structured mentoring, and reflective pedagogy in ensuring equitable and meaningful teaching internship experiences.